1998
DOI: 10.1523/jneurosci.18-02-00625.1998
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Proteins to Postsynaptic Densities after Transient Cerebral Ischemia

Abstract: Transient ischemia leads to changes in synaptic efficacy and results in selective neuronal damage during the postischemic phase, although the mechanisms are not fully understood. The protein composition and ultrastructure of postsynaptic densities (PSDs) were studied by using a rat transient ischemic model. We found that a brief ischemic episode induced a marked accumulation in PSDs of the protein assembly ATPases, N-ethylmaleimide-sensitive fusion protein, and heat-shock cognate protein-70 as well as the BDNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
131
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(148 citation statements)
references
References 70 publications
17
131
0
Order By: Relevance
“…This translocation of chelatable zinc ions from presynaptic terminals to postsynaptic neurons has been proposed to play an important role in the selective neuronal death resulting from ischemia, status epilepticus and trauma Tonder et al 1990;Koh et al 1996;Suh et al 2000; except for Cole et al 2000). Consistent with our in vitro observation that zinc ions promote the assembly of the PSD, after transient cerebral ischemia, a condition that lead to the accumulation of chelatable zinc in neurons (Tonder et al 1990;Koh et al 1996), the PSDs of hippocampal neurons became significantly thicker (Hu et al 1998). Similarly, after stimulation with high concentrations of KCl and with glutamate, treatments that also probably resulted in the translocation of presynaptic zinc to the postsynaptic neurons (Assaf and Chung 1984), PSDs in hippocampal neurons became thicker (Dosemeci et al 2001).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This translocation of chelatable zinc ions from presynaptic terminals to postsynaptic neurons has been proposed to play an important role in the selective neuronal death resulting from ischemia, status epilepticus and trauma Tonder et al 1990;Koh et al 1996;Suh et al 2000; except for Cole et al 2000). Consistent with our in vitro observation that zinc ions promote the assembly of the PSD, after transient cerebral ischemia, a condition that lead to the accumulation of chelatable zinc in neurons (Tonder et al 1990;Koh et al 1996), the PSDs of hippocampal neurons became significantly thicker (Hu et al 1998). Similarly, after stimulation with high concentrations of KCl and with glutamate, treatments that also probably resulted in the translocation of presynaptic zinc to the postsynaptic neurons (Assaf and Chung 1984), PSDs in hippocampal neurons became thicker (Dosemeci et al 2001).…”
Section: Discussionsupporting
confidence: 86%
“…cross-sectional area, thickness and curvature, and the protein content of the PSD (e.g. Greenough et al 1978;Rutledge 1978;Rees et al 1985;Strevaag and Greenough 1985;Desmond and Levy 1986;Strack et al 1997;Hu et al 1998;Dosemeci et al 2001; except for the study of Sorra and Harris 1998). Time-lapse recording of the clusters of green fluorescence protein PSD95 in hippocampal neurons revealed rapid formation and remodeling of the PSD (Marrs et al 2001).…”
mentioning
confidence: 99%
“…The presence of brevican in this fraction has already been reported (Seidenbecher et al 1998;Niederöst et al 1999) and it was suggested to contribute to the nonpermissive properties of CNS myelin (Niederöst et al 1999). The light membrane fraction is a less well defined membrane subpopulation, which contains a mixture of endoplasmic reticulum, Golgi and plasma membranes as estimated by electron microscopy (Cohen et al 1977;Hu et al 1998). This fraction contains extrasynaptic marker molecules of neuronal membranes, such as BDNF receptor gp145trkB and gp95trkB or the 5-hydroxytryptamine receptor 2A (Hu et al (b) (a) Fig.…”
Section: Discussionmentioning
confidence: 84%
“…However, ischemic conditions have since been shown to induce the formation of self-associated CaMKII clusters in a variety of systems (Dosemeci et al, 2000;Tao-Cheng et al, 2002;Hudmon et al, 1996), and it has been demonstrated that these clusters contaminate PSD-enriched fractions (Dosemeci et al, 2000). Since it has been shown that in vivo ischemia increases the thickness of the PSD (Hu et al, 1998), and that an in vitro ischemic treatment induces both CaMKII clustering and an increase in CaMKII labeling at the PSD (which correlates with an increase in PSD thickness) (Dosemeci et al, 2000), it is likely that the increase in CaMKII concentration in PSD-enriched fractions that we and others have observed represents both CaMKII translocation to the PSD and cluster formation.…”
Section: Discussionmentioning
confidence: 99%